EFEKTIVITAS CHATBOT EDUKASI KESEHATAN REPRODUKSI TERHADAP PENGETAHUAN DAN SIKAP PENCEGAHAN ANEMIA PADA REMAJA PUTRI SMP DI KOTA MAKASSAR - Dia Rejeki Utami; Nuryanti Thahir; Muhammad Syahrul Alam (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Anemia among adolescent girls remains a major public health problem that may affect growth, academic performance, reproductive health, and future maternal outcomes. Digital health technologies, including chatbots, have emerged as innovative educational tools because they provide interactive, accessible, and personalized health information. Recent evidence indicates that chatbot-based health education effectively improves adolescents' knowledge and attitudes toward reproductive health and anemia prevention. This study aimed to determine the effectiveness of a reproductive health education chatbot on knowledge and attitudes regarding anemia prevention among junior high school girls in Makassar City. A quantitative pre-experimental one group pretest-posttest design was employed involving 60 female students selected using purposive sampling. Data were collected using knowledge questionnaires, attitude questionnaires, and chatbot utilization records. Data analysis included descriptive statistics, Shapiro-Wilk normality test, and Paired Sample t-Test. The findings demonstrated that the mean knowledge score increased from 63.42 ± 9.85 to 84.27 ± 7.31, while the mean attitude score improved from 65.18 ± 8.92 to 86.14 ± 6.75. Paired Sample t-Test revealed a statistically significant difference (p = 0.001). Therefore, chatbot-based reproductive health education is effective in improving knowledge and attitudes toward anemia prevention among adolescent girls.